DEVELOPMENT OF AN EXTRACTION METHOD OF GOLDEN BERRY (Physalis peruviana L.) POLYPHENOL OXIDASE AND ISOLATION BY AQUEOUS TWO-PHASE SYSTEM - BRAVO M., Karent E.; MUÑOZ D., Katalina; CALDERÓN G., Jénifer; OSORIO D., Edison J. (Vitae, 2011)
Polyphenol oxidase activity is responsible for the enzymatic browning of fruits and vegetables, and the end products of the catalyzed reaction are detrimental to food quality, in both sensory and nutritional properties. In this study we evaluated the influence of the extraction conditions (pH, concentration, composition of extraction buffer and protein precipitation agent) on the activity of golden berry polyphenol oxidase. The extraction of proteins with a mixture of Triton® X-100 and polyvinyl pyrrolidone in 0.2 M phosphate buffer at pH 6.0 and precipitation with cold acetone in a ratio supernatant-acetone of 1:1 gave the higher polyphenol oxidase activity. Partial purification of polyphenol oxidase was achieved using an aqueous two-phase system composed by polyethylene glycol and phosphate. Effect of phase composition, molecular weight of polythylene glycol and pH of the system on enzyme partitioning was studied. The optimum system was found at pH 5.5 containing 5% polythylene glycol 8000 and 14% phosphate, with Ka of 4.70, purification factor of 4.65 and a 74.29% yield of enzyme activity in the top phase. These results show a significant effect of extraction conditions on polyphenol oxidase activity and provide a quick, simple and efficient method for polyphenol oxidase isolation.